Innovative methods of eliminating the conflict of relations in management and personnel - Kosenko, A. V.; Dolina, I. V.; Pererva, P. G. (Видавничий дім "Києво-Могилянська академія", 2023)
It has been proven that options for conflict are lack of resources in the external environment, which forces the organization to work in conditions of scarcity of resources, and in the internal environment there will also be a need to fight for them. The current view is that even in well-managed organizations, some conflict is not only possible, but even desirable.
Інноваційні методи усунення конфліктності відносин в управлінні та персоналі
Keywords: personnel management; conflictology; management psychology; production; efficiency